Strategies of the beetle Oochrotus unicolor (Tenebrionidae) thriving in the waste dumps of seed‐harvesting Messor ants (Formicidae). (23rd December 2019) - Parmentier, Thomas; Gaju‐Ricart, Miquel; Wenseleers, Tom; Molero‐Baltanás, Rafael
Abstract : 1. A diverse group of arthropods have adapted to the niches found inside the nests of social insects. Studies mostly focused on very specialised parasites residing in the brood chambers. However, the biology and strategies of symbionts occupying other niches, such as waste dumps, are underexplored. 2. Using a series of complementary experiments, this study demonstrated that the Mediterranean beetle Oochrotus unicolor has adapted to the waste dump niche found in the nests of Messor harvester ants. 3. Laboratory experiments confirmed field observations that the beetle preferentially resided in the refuse pits. Next, it was shown that the beetles readily consumed seeds and flour, whereas other food sources were poorly accepted and ant brood was never even eaten. The beetles did not elicit a strong aggression response in Messor ants, and they could tolerate very high densities of workers without clear costs. The beetles modestly mimicked the nest recognition cues of their Messor host. This imperfect mimicry could promote the adoption of the beetle in the ant colony, in concert with mechanical defence generated by its tank‐like body. Isolation of the beetle from its host did not significantly affect the beetle's chemical cuticular profile nor did it provoke elevated ant aggression, indicating that the beetle does not acquire the chemicals passively from its host. 4. This paper discusses the fact that waste dumps in social insect nests are hotspots for arthropod symbionts. It shows that symbionts in this niche may employ behavioural, trophic and chemical strategies that are different from those found in other niches of social insect nests. Abstract : The Mediterranean beetle Oochrotus unicolor is an obligate nest associate of Messor harvester ants. The beetles preferentially resided in the waste dumps of Messor ants. Their diet mainly consists of seeds. They modestly mimicked the nest recognition cues of their host. Symbionts in waste dumps of social insects may employ behavioural, trophic, and chemical strategies that are different from those found in other niches in the nests of social insects.